Comparing Different Delivery Routes for Stem Cell Therapy in Urology : A Systematic Review - Jody Fajar Hibatullah; Teuku Zulbahraini; Debby Sofiana (International Medical Journal Corp. Ltd, 2025)
Introduction: Stem cell therapy shows significant promise for various urological diseases, including erectile dysfunction, stress urinary incontinence, and chronic kidney disease. However, the optimal delivery route—a critical factor for therapeutic success and safety—remains poorly defined due to a lack of direct comparative evidence. This systematic review aims to comprehensively evaluate and compare the different administration routes for stem cell therapy in urological conditions. Methods: Following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines , a systematic search was conducted across PubMed, Semantic Scholar, Springer, Google Scholar, and Wiley Online Library. Inclusion criteria targeted clinical studies on human subjects that evaluated stem cell therapy for urological conditions and compared at least two delivery routes or provided clear methodological details. After screening 533 records, 17 studies were included in the final analysis. Results: Localized delivery routes, such as intracavernous or transurethral injections, demonstrated significant functional improvements for erectile dysfunction and stress urinary incontinence, respectively, with no serious adverse events reported. Systemic administration via intravenous or intra-arterial routes led to statistically significant improvements in renal function for patients with chronic kidney disease, also with a favorable safety profile. Intrathecal delivery for neuro-urological conditions showed mixed efficacy and was associated with transient, non-serious side effects like headache and fever. A major limitation was the frequent omission of delivery route details in many of the analyzed studies. Conclusion: Stem cell therapy is a promising and generally safe treatment modality for a range of urological diseases. The evidence suggests that the ideal delivery route should be tailored to the specific pathology: direct local injections appear optimal for focal conditions, while systemic routes are suited for diffuse diseases. However, the field is critically hampered by a lack of head-to-head comparative trials and inconsistent methodological reporting. Rigorous, standardized comparative research is urgently needed to establish optimal delivery strategies and advance clinical practice.